2021
DOI: 10.1080/10615806.2021.1952191
|View full text |Cite
|
Sign up to set email alerts
|

Depression and anxiety in cardiac rehabilitation: differential associations with changes in exercise capacity and quality of life

Abstract: Background: Cardiac rehabilitation (CR) has been successful in improving exercise capacity (EC) and quality of life (QoL). However, depression and anxiety are highly prevalent among cardiac patients and might represent risk factors for rehabilitation outcomes. The aim of this study was to investigate the role of depression and anxiety as possible independent risk factors for CR outcomes. Methods: The study applied a pre-post-design. The sample comprised N = 3'434 cardiac disease patients taking part in a Swiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 52 publications
0
4
0
1
Order By: Relevance
“…Quality of life was measured at the beginning of rehabilitation with the MacNew Heart Disease Quality of Life Questionnaire (MacNew Heart;Höfer, Lim, Guyatt, & Oldridge, 2004). The subscales follow the factorial structure proposed by Bermudez et al (2021a). Tania Bermudez et al…”
Section: Results For Lpamentioning
confidence: 99%
See 2 more Smart Citations
“…Quality of life was measured at the beginning of rehabilitation with the MacNew Heart Disease Quality of Life Questionnaire (MacNew Heart;Höfer, Lim, Guyatt, & Oldridge, 2004). The subscales follow the factorial structure proposed by Bermudez et al (2021a). Tania Bermudez et al…”
Section: Results For Lpamentioning
confidence: 99%
“…Thus, one potential explanation for the direction of the associations might be the high correlations at the interindividual level between anxiety, adjustment disorder and depressive symptoms (see Table 2). Yet, given that previous studies reported positive effects of anxiety symptoms on improvements in exercise capacity and in physical quality of life during rehabilitation (Bermudez et al, 2021a), a second explanation might still be that the strong overlap between depression symptoms, adjustment disorder and anxiety might mask the unique effects that only show when the other constructs are controlled for. Yet, all results should be interpreted very carefully at the interindividual level given the very high interindividual correlations between the different symptoms, and the association between anxiety and PA/SB should surely be investigated further.…”
Section: Psychological Medicine 5997mentioning
confidence: 99%
See 1 more Smart Citation
“…Based on previous research and clinical experience, we controlled for the following psychosocial and disease-related covariates: housing situation (living alone vs. living with others), presence of a psychiatric disorder, change in 6-minute-walk distance (calculated using the difference between the walk distance at CR entry and discharge), ischemic heart disease and modifiable traditional cardiovascular risk factors (hypertension, dyslipidemia, overweight, smoking and type II diabetes). Social support (assessed with housing situation as a proxy) is reportedly associated with higher psychological well-being and prevention of emotional distress after cardiac disease [ 42 , 43 ], while the presence of a psychiatric disorder impacts negatively on CR outcomes [ 44 ]. With regard to the 6MWD, better 6MWD performance has been linked to greater HRQoL improvements [ 13 , 41 ].…”
Section: Methodsmentioning
confidence: 99%
“…В основе понимания развития психосоматического компонента болезни лежит тезис: ответные реакции на стресс являются связующим звеном между мозгом, чувствами, поведением и биологическими реакциями, влияющие на физическое самочувствие [1][2][3].…”
unclassified